Bullying involvement and suicidal ideation in elementary school children across Europe - Husky, Mathilde M.; Bitfoi, Adina; Carta, Mauro Giovanni; Gölitz, Dietmar; Koç, Ceren; Lesinskiene, Sigita; Mihova, Zlatka; Otten, Roy; Kovess-Masfety, Viviane (Journal of Affective Disorders, 2022)
Background: Bullying involvement is associated with suicidal ideation among adolescents, yet there are no studies examining this issue among younger children. Methods: The School Children Mental Health in Europe study was conducted in seven countries in 2010 using similar methods to collect cross-sectional data from children, parents, and teachers. Suicidal ideation and thoughts of death were assessed using the Dominic Interactive among children. Parent and teacher reports were used to determine bullying involvement. The sample comprised n = 5,183 children ages 6 to 11 identified as bullies (n = 740, 14.3%), victims (n = 945, 18.2%), bully-victims (n = 984, 18.2%) and not involved in bullying (n = 2,514, 48.5%). Multivariate logistic regressions were used to assess the association of bullying involvement with suicidal ideation and thoughts of death. Results: Suicidal ideation was reported by 13.3% of those not involved in bullying, 17.1% of victims, 19.6% of bullies and 24.4% of bully-victims. Similarly, thoughts of death were reported by 19.0% of victims, 24.3% of bullies, and 25.0% of bully-victims. Children identified as being involved were more likely than those not involved to report suicidal ideation in bivariate analyses. When controlling for psychopathology and for maternal distress among other factors, the association remained significant for bullies (AOR=1.30, 95%CI=1.01–1.66), bully-victims (AOR=1.54, 95%CI=1.22–1.94), but not for victims (AOR=1.02, 95%CI=0.80–1.30). Limitations: The study is cross-sectional. The assessment of bullying may have underestimated victimization. Conclusions: The association of bullying involvement and child suicidal ideation is present among elementary school children across Europe, using multiple informants to avoid shared variance biases, and adjusting for key factors.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Bullying; Children; Cross-national; Elementary school; Mental health; Suicidal ideation